The effect of Rahn on women’s economic empowerment: a case study in Kota Bharu, Kelantan - Zahari, A’dilah; Hassan, Rusni (Journal of Global Business and Social Entrepreneurship (GBSE), 2017)
A large number of study on the impact of rahn product has been conducted and the result shown that rahn is a significant tool in empowering economic and social aspects of its subscribers. However, there are very limited study that analyzed, examined on the effect of rahn on women particularly in enhancing their economic and social status. Thus, this study aim is to explore and analyze the economic consequences of rahn among women within the district of Kota Bharu, Kelantan. In doing so, this study will examine the factors in determining women’s participation on rahn and also analyze specifically the impact of rahn on the women economic empowerment. A total of 300 self-administered questionnaires were distributed personally and a number of 225 questionnaires were returned which considered as usable for the purposes of this study. The responses also were analyzed using descriptive analysis via SPSS version 22, thereby yielding a response rate of 75 percent. Overall, the findings of survey demonstrated that access to rahn has contributed immensely to the women economic empowerment. It is important to examine this aspect of women empowerment taking into consideration that their contribution is fully significant which cannot be undeniable. This is can be demonstrated through rahn services as an effectiveness instruments in developing women entrepreneurial skills and thus it empowered them in economically and socially.